Varieties of Capital-Market Crises - Guillermo A. Calvo (Inter-American Development Bank, Office of the Chief Economist, 1995)
In this post-modern world of high capital mobility, countries are being disciplined by the anonymous capital market. One view of the situation -perhaps the prevalent view among economists- is that Wall Street gets into your hair because you are running an unsustainable economic program and crises are bound to happen. A polar view is that countries are at the mercy of the capital market. This paper attempts to bring these views under one roof, putting special emphasis on balance-of-payment crises.
Keywords: 330